2018
DOI: 10.1021/acs.jmedchem.8b00047
|View full text |Cite
|
Sign up to set email alerts
|

A Structure–Activity Relationship Study of Bitopic N6-Substituted Adenosine Derivatives as Biased Adenosine A1 Receptor Agonists

Abstract: The adenosine A receptor (AAR) is a potential novel therapeutic target for myocardial ischemia-reperfusion injury. However, to date, clinical translation of prototypical AAR agonists has been hindered due to dose limiting adverse effects. Recently, we demonstrated that the biased bitopic agonist 1, consisting of an adenosine pharmacophore linked to an allosteric moiety, could stimulate cardioprotective AAR signaling in the absence of unwanted bradycardia. Therefore, this study aimed to investigate the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…However, as predicted from the in vivo cardiovascular data obtained in the present manuscript, VCP746 was also a potent and high efficacy agonist of A 2A ‐mediated CRE‐SPAP responses. An agonist effect of VCP746 on cAMP formation at A 2A ‐receptors has also been reported recently in CHO cells (Aurelio et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…However, as predicted from the in vivo cardiovascular data obtained in the present manuscript, VCP746 was also a potent and high efficacy agonist of A 2A ‐mediated CRE‐SPAP responses. An agonist effect of VCP746 on cAMP formation at A 2A ‐receptors has also been reported recently in CHO cells (Aurelio et al, ).…”
Section: Discussionsupporting
confidence: 60%
“… Moya et al (2007) examined functional selectivity profiles for a series of phenethylamine and phenylisopropylamine derivatives at human 5-HT 2A and 5-HT 2C receptors and found that subtle changes in ligand structure resulted in pronounced difference in cellular signaling profiles. These data highlight the need for careful ligand structure-functional selectivity relationship studies to improve our understanding of the molecular mechanisms that underlie functional selectivity ( Chen et al, 2012 ; Shonberg et al, 2013 ; Szabo et al, 2014 ; White et al, 2014 ; Chang et al, 2015 ; Lovell et al, 2015 ; Baltos et al, 2016 ; Manglik et al, 2016 ; Männel et al, 2017 ; Aurelio et al, 2018 ; Chun et al, 2018 ).…”
Section: Functional Selectivity / Biased Agonismmentioning
confidence: 99%
“…If a quantitative scale of bias is employed then a simple correlation of DDLog(t/K A ) values can be useful. Figure 12 shows DDLog(t/K A ) values for a series of bitopic adenosine A 1 receptor agonists (referenced to NECA [1-(6-amino-9H-purin-9-yl)-1-deoxy-N-ethyl-b-Dribofuranuronamide]) for calcium and cAMP responses; it can be seen that while eight compounds correlate fairly well [uniform DDLog(t/K A ) values], the eight compounds in red are biased toward cAMP over calcium (Aurelio et al, 2018). Other methods are used if more than one signaling pathway is involved.…”
Section: G Representations Of Biased Signaling Profilesmentioning
confidence: 99%
“…Agonists denoted with black solid circles show uniform activation of both pathways (no bias), whereas circles in red indicate bias toward cAMP signaling over calcium. Data redrawn fromAurelio et al (2018).…”
mentioning
confidence: 99%